The Gift of Reason: St. Irenaeus and John Paul II in Dialogue - Francois, Jacob (Teologia w Polsce, 2022)
St. Irenaeus as a western figure has a different exegetical account of Genesis which provides some of the foundational principles for his theological concepts of the ‘new Adam’ and recapitulation. The western theological tradition has instead taken the approach handed down by St. Augustine which is seen in St. John Paul II’s Theology of the Body. This article will describe the difficulties of Irenaeus’s view while also showing the faults of the Augustinian position as shown in John Paul II while comparing the fruit of both in order to develop a synthesis that can encapsulate the fruit of both positions.